Haplotype Structure, LD Blocks, and Uneven Recombination Within the LRP5 Gene - Twells, Rebecca C.J.; Mein, Charles A.; Phillips, Michael S.; Hess, J. Fred; Veijola, Riitta; Gilbey, Matthew; Bright, Matthew; Metzker, Michael; Lie, Benedicte A.; Kingsnorth, Amanda; Gregory, Edward; Nakagawa, Yusuke; et al. (Genome Research, 2003)
Patterns of linkage disequilibrium (LD) in the human genome are beginning to be characterized, with a paucity of haplotype diversity in “LD blocks,” interspersed by apparent “hot spots” of recombination. Previously, we cloned and physically characterized thelow-density lipoprotein-receptor-related protein 5(LRP5) gene. Here, we have extensively analysed bothLRP5 and its flanking three genes, spanning 269 kb, for single nucleotide polymorphisms (SNPs), and we present a comprehensive SNP map comprising 95 polymorphisms. Analysis revealed high levels of recombination across LRP5, including a hot-spot region from intron 1 to intron 7 of LRP5, where there are 109 recombinants/Mb (4882 meioses), in contrast to flanking regions of 14.6 recombinants/Mb. This region of high recombination could be delineated into three to four hot spots, one within a 601-bp interval. ForLRP5, three haplotype blocks were identified, flanked by the hot spots. Each LD block comprised over 80% common haplotypes, concurring with a previous study of 14 genes that showed that common haplotypes account for at least 80% of all haplotypes. The identification of hot spots in between these LD blocks provides additional evidence that LD blocks are separated by areas of higher recombination.[Supplementary material: primers are available from our Web site:http://www-gene.cimr.cam.ac.uk/todd/human_data.shtml.]